The ABC model for telework in Portugal - Gonçalves, Rui M. R. (2012)
The principal aim of this paper is to develop a simple and objective model which can classify an systematise telework, and provide a standard for Portugal. This model defines special concepts of telework and allows the division of the activity in this area, making its application easier. The model was constructed on the basis of four perspectives which it has to cover: the economic and social, of the employers, of the teleworkers and the suppliers of goods and services.